W.C. Fields [videorecording (DVD)] : 6 short films. - Fields, W. C. (William Claude), 1880-1946; Middleton, Edwin; Brice, Monte, 1891-1962; Pearce, Leslie; Bruckman, Clyde, 1894-1955; Ripley, Arthur, 1895-1961 (Criterion collection, 2000)
This compilation of films pays tribute to America's cantankerous comedy genius, W.C. Fields. Legendary one-liners and slapstick routines are preserved in these early shorts that chronicle the development of Fields' irascible screen persona.